Nugroho1, Hardati2, (2025). Penghidupan Berkelanjutan Kepala Keluarga Penerima Redistribusi Tanah di Kecamatn Getasan Kabupaten Semarang : - - Nugroho, Rahayu Syafira; Hardati, Puji (Jurnal Sains Geografi, 2025)
Land redistribution is implemented to address land tenure inequality that limits farmers’ access to resources and economic opportunities. This study examines household distribution, land use and ownership, and the livelihood conditions of redistribution beneficiaries in Getasan Subdistrict. Using quantitative methods with spatial and descriptive analysis of five livelihood assets, the study finds that redistributed lands are concentrated in Tajuk and Kopeng. Tajuk is dominated by livestock, while Kopeng focuses on agriculture. Most beneficiaries retain ownership and manage their land independently. The program supports sustainable livelihoods, though improved access to training, capital, and local institutions remains essential.